Institutionalization of professional sociological education in Belarus: origins and prospects - Danilov, Alexander N. (Journal of the Belarusian State University. Sociology, 2019)
The article is devoted to the history of institutionalization of professional sociological education in Belarus. It is noted that the opening in 1989 of the department of sociology and the Department of sociology at the newly established philosophical and economic faculty of the Belarusian State University (since 1999 – the faculty of philosophy and social sciences) was a significant event in the history of science and education. It allowed to complete the institutionalization of sociological education and to begin training of professional sociological personnel in Belarus. The subsequent development of the system of university sociological education showed the correctness of the decision taken 30 years ago. The teaching staff of the department of sociology, graduates of the department contribute to the training of highly qualified specialists-sociologists, the development of sociology, in the sustainable functioning of modern society.